2021
DOI: 10.3389/fonc.2021.740985
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Prognostic Model in Transitional Bladder Cancer Based on Inflammatory Response-Associated Genes

Abstract: BackgroundBladder cancer is a common malignant type in the world, and over 90% are transitional cell carcinoma. While the impact of inflammatory response on cancer progression has been reported, the role of inflammatory response-associated genes (IRAGs) in transitional bladder cancer still needs to be understood.MethodsIn this study, IRAGs were download from Molecular Signature Database (MSigDB). The transcriptional expression and matched clinicopathological data were separately obtained from public databases.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…In the same context, L. Yang et al proposed a nine-gene prognostic model to enhance the prognosis prediction of BCa, achieving an AUC value of 0.76 at five years on the training set and a value of 0.63 for the same time on the test set [ 127 ]. In another study, Z. Xie et al suggested a 10-inflammatory response-associated gene prognostic model which reached AUC values of 0.71 and 0.67 at year one in the TCGA-BCa and GSE13507 cohorts, respectively [ 128 ]. Furthermore, J. Lin et al constructed an 11-gene prognostic model for predicting overall survival in BCa patients, reaching 1/3/5-year AUC values of 0.686/0.665/0.666, 0.800/0.742/0.697, 0.826/0.792/0.763, and 0.781/0.831/0.839 for the TCGA-BCa, GSE13507, GSE32548, and GSE32894 cohorts, respectively [ 129 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the same context, L. Yang et al proposed a nine-gene prognostic model to enhance the prognosis prediction of BCa, achieving an AUC value of 0.76 at five years on the training set and a value of 0.63 for the same time on the test set [ 127 ]. In another study, Z. Xie et al suggested a 10-inflammatory response-associated gene prognostic model which reached AUC values of 0.71 and 0.67 at year one in the TCGA-BCa and GSE13507 cohorts, respectively [ 128 ]. Furthermore, J. Lin et al constructed an 11-gene prognostic model for predicting overall survival in BCa patients, reaching 1/3/5-year AUC values of 0.686/0.665/0.666, 0.800/0.742/0.697, 0.826/0.792/0.763, and 0.781/0.831/0.839 for the TCGA-BCa, GSE13507, GSE32548, and GSE32894 cohorts, respectively [ 129 ].…”
Section: Discussionmentioning
confidence: 99%
“…For exploring more potential inflammatory response-related targets and mechanisms in development of tumor, similar risk models were successfully constructed in many cancers, such as nephroblastoma and bladder cancer [ 29 , 30 ]. Inflammatory diseases are linked to lncRNAs, which might be used as biomarkers to diagnose inflammatory diseases such as rheumatoid arthritis [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have mainly focused on urinary biomarkers in diagnosis and monitoring, such as urine DNA methylation assay, while inflammatory biomarkers in the blood have also recently been demonstrated to be potential biomarkers in prognosis of BC patients, such as plasma fibrinogen and D-dimer [32][33][34]. Currently, a prognostic risk model based on the inflammatory response associated with mRNA may effectively distinguish BC patients with a good or worse prognosis [30]. IRRlncRNAs, on the other hand, have yet to be identified as predictive markers for BC.…”
Section: Discussionmentioning
confidence: 99%
“…The immune and inflammatory process is dynamic and changing over time, reflecting the degree of the normal or abnormal responses of the body. Although increasing research has focused on the molecular characteristics of BLCA based on gene expression patterns of immune or inflammation (15)(16)(17)(18)(19), there has been no report of prognosis-related classification that combined immune with inflammatory response patterns. Therefore, it is meaningful to identify the distinct IIR patterns and develop a novel prognosis, immunotherapy, and chemotherapy-related signature based on IIR patterns.…”
Section: Introductionmentioning
confidence: 99%